2016
DOI: 10.1158/1541-7786.mcr-15-0425-t
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a Exerts Differential Effects on Melanoma Growth and Metastatization

Abstract: Malignant melanoma is the most aggressive form of skin cancer; therefore, it is crucial to disclose its underlying molecular mechanisms. MicroRNAs (miRNAs) are small endogenous noncoding RNAs able to posttranscriptionally downregulate the expression of direct target genes. Using a melanoma progression model, miR-146a was identified as a key double-acting player in melanoma malignancy. In fact, miR-146a is able to enhance tumor growth, while it suppresses dissemination. It was determined that miR-146a coordinat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 48 publications
(23 reference statements)
4
34
0
Order By: Relevance
“…Numb has been shown to be targeted by miR‐146 family members and by miR‐34a in previous studies . Reporter assays in this study specifically show that Numb is targeted by miR‐31, miR‐96 , and miR‐182 both individually and concordantly.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Numb has been shown to be targeted by miR‐146 family members and by miR‐34a in previous studies . Reporter assays in this study specifically show that Numb is targeted by miR‐31, miR‐96 , and miR‐182 both individually and concordantly.…”
Section: Discussionsupporting
confidence: 59%
“…14,[40][41][42][43] It is well known that miR-146 family members are able to target the Numb gene and these interactions are involved in driving tissue differentiation and disease pathogenesis. 14,36,[44][45][46] In this study, we show that there is concordant upregulation of miR-31, miR-96, and miR-182 in HNSCC. Furthermore, Numb isoforms 1 to 4 possess similar activity and are able to suppress in vitro transformation.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Further work supported these findings, and concluded lunatic fringe (LFNG) was also a direct target gene in melanoma cells. Melanoma recurrence correlated with miR‐146a levels (Raimo et al, ). Other investigators confirmed using transwell assays that miR‐146a could also promote malignant melanoma migration and invasion.…”
Section: Role Of Mir‐146a In Specific Cancersmentioning
confidence: 99%
“…Its upregulation during melanoma progression triggers tumor growth through inhibition of lunatic fringe (LFNG) and NUMB and activation of the NOTCH/PTEN/AKT pathway. In contrast its downregulation in Circulating Tumor Cells (CTC), suppresses tumor dissemination through modulation of the expression of ITGAV and ROCK1 [62, 63]. miR-638 is able to promote melanoma metastasis since it is overexpressed in metastatic lesions compared to primary melanomas [64].…”
Section: Microrna Deregulation In Melanoma Development and Progressionmentioning
confidence: 99%